Regulation of normal differentiation in mouse and human myeloid leukemic cells by phorbol esters and the mechanism of tumor promotion - Lotem, Joseph (1979)
The control of cell multiplication and differentiation by tumor-promoting phorbol esters including 12-O-tetradecanoylphorbol-13-acetate (TPA) has been studied with different clones of mouse myeloid leukemic cells, a line of human myeloid leukemic cells, and normal mouse bone marrow myeloblasts. TPA induced normal cell differentiation in one of the mouse leukemic clones and this was mediated by induction of the protein inducer of differentiation to macrophages or granulocytes (MGI) in the cells that then differentiated. Other mouse clones were not induced to differentiate by TPA. In one of these clones, TPA induced cell susceptibility to externally added MGI. This effect was not due to a general induction of susceptibility to all compounds because TPA did not induce susceptibility to lypopolysaccharide or dexamethasone in this clone. In the human leukemic cell line, TPA also induced differentiation with the induction of MGI activity and enhanced susceptibility to added MGI. It is suggested that the clonal differences in induction of MGI activity and increased susceptibility to MGI may be associated with differences in receptors for TPA and the ability of TPA to modify receptors for MGI. Studies with normal bone marrow cells have indicated that TPA stimulated MGI activity and also increased susceptibility of normal myeloblasts to induction of multiplication by MGI. The ability of different phorbol esters to produce these effects on normal myeloblasts and myeloid leukemic cells paralleled their ability to act as tumor promoters. The results indicate that a tumor promoter such as TPA can induce the production of and increase cell susceptibility to a normal regulator of cell multiplication and differentiation. TPA has pleiotropic effects. It is suggested that, by these mechanisms, TPA may thus act as a tumor promoter by increasing cell multiplication in initiated cells, induce differentiation in some cells, or inhibit differentiation in other cells, depending on which molecules are being regulated in the TPA-treated cells.